PERLINDUNGAN HUKUM BAGI KREDITUR ATAS JAMINAN SERTIFIKAT HAK GUNA BANGUNAN YANG BERDIRI DI ATAS HAK PENGELOLAAN - Prasetya, Rangga Dwi; Wahyu Utomo, Hatta Isnaini (Faculty of Law, Universitas Muhammadiyah Pontianak, 2019)
Management Rights Title is the right to control over the land from the state authority delegated to the holder partial implementation. Land with Management Rights Title may be granted to another party one through Building Rights Title. The whole provisions governing Building Rights Title generally applies to Building Rights Title on the land Management Right Title. No Regulation Legislation that specifically regulates the building standing on the Management Rights raises the issue of how if Building Rights Title will serve as collateral and then how protection for creditors at the time of going to execute if the party becomes the debtor defaults.